Degradation Mechanism and Lifetime Improvement Strategy for Blue Phosphorescent Organic Light‐Emitting Diodes. Issue 9 (21st March 2017) - Song, Wook; Lee, Jun Yeob
Abstract : Providing adequate lifetimes for organic light‐emitting diodes (OLEDs) has been a challenging issue for a long time because of the naturally weak chemical bonds of organic materials that can be damaged during electrical processes that drive light emission. The lifetime of OLEDs has been dramatically extended to the point where commercialization is feasible due to the development of stable materials and device structures that lessen the damage of the organic materials. However, the lifetime of high efficiency OLEDs represented by phosphorescent OLEDs is still short, and this prevents full utilization in red, green and blue colors. The lifetime of the blue phosphorescent OLEDs is particularly short, i.e., less than one tenth of the lifetime of conventional blue fluorescent OLEDs. Therefore, a large increase in the lifetime of the blue phosphorescent OLEDs is essential. In this work, recent results on the degradation mechanism and operational stability of blue phosphorescent OLEDs are reviewed by classifying them into material and device related approaches. In addition, ideal material and device plans to reach the lifetimes required for commercialization in blue phosphorescent OLEDs are proposed. Abstract : Recent results reporting the degradation mechanism and operational stability of blue phosphorescent OLEDs are reviewed by classifying them into material and device related approaches. In addition, ideal material and device plans to reach the commercialization lifetime level in blue phosphorescent OLEDs are proposed.